2019
DOI: 10.1016/j.carbon.2018.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the sub-processes in laser reduction of graphene oxide by adjusting the power and scanning speed of laser

Abstract: Laser reduction of graphene oxide is a promising technology for manufacturing advanced devices such as supercapacitors, sensors and transistors, owing to its distinctive advantages in selective and localized GO reduction, direct micro-nanoscale patterning, and no requirement for chemicals. However, the fundamental mechanism underlying the laser induced reduction is still not well understood. In this paper, we demonstrate that by adjusting the power and scanning speed of a 780 nm femtosecond laser, not only can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 76 publications
4
64
0
3
Order By: Relevance
“…In single-layer pristine graphene, the ratio I2D/IG is ~2-3, and it decreases as the number of layers increase [47]. On this basis, the results of the rGO sheets showed that the rGO produced with the CO2 laser presents a lower number of layers (higher I2D/IG ratio) than the one induced with the UV laser, which might be related to its lower thickness (~12 μm, in comparison with ~18 μm, according to profilometry results) due to the higher irradiation power, as demonstrated in other works [48]. In addition, the lower FWHM2D also indicates that these layers have a better crystallographic structure [49].…”
Section: Resultssupporting
confidence: 65%
“…In single-layer pristine graphene, the ratio I2D/IG is ~2-3, and it decreases as the number of layers increase [47]. On this basis, the results of the rGO sheets showed that the rGO produced with the CO2 laser presents a lower number of layers (higher I2D/IG ratio) than the one induced with the UV laser, which might be related to its lower thickness (~12 μm, in comparison with ~18 μm, according to profilometry results) due to the higher irradiation power, as demonstrated in other works [48]. In addition, the lower FWHM2D also indicates that these layers have a better crystallographic structure [49].…”
Section: Resultssupporting
confidence: 65%
“…The laser is only used for the fabrication of the samples and it is not involved in the electrical measurements carried out for the characterization of the resistive switching of the devices. Starting with the bare GO film, the laser triggers a photothermal reduction process that removes oxygen-containing functional groups (increasing the atomic percentage of carbon) and partially recovers the sp 2 hybridized carbon-carbon bonds, increasing the conductivity of the nanographene flakes according to the laser power [28]. The laser power can be adjusted to modulate the conductivity of the samples leading to different levels of reduction.…”
Section: Methodsmentioning
confidence: 99%
“…The laser-scribing process was performed at room temperature with a controlled relative humidity of 50% and a constant airflow forced by a fume extractor system. These conditions avoid any intentional doping during the lithographic process; however, the intentional doping/functionalization of the devices by setting an appropriate environment during the laser-scribing process [28,29] constitutes a path to be explored for boosting the performance of this type of devices. Micro drops of bare conductive electric paint TM or Ag-based conductive paint were placed as electrodes to define the electrical access and to avoid any damage on the active GO material when contacting the devices with probes.…”
Section: Methodsmentioning
confidence: 99%
“…The chemical alterations induced by the laser photothermal process were also studied by XPS. As was expected, the laser reduction led to a dramatic change in the original carbon–oxygen compounds of the GO layer [28,29]. Thus, the initial carbon atomic content of ~52% increased up to 90% after the laser reduction process, whereas the oxygen presented a decrease from ~45% before the photothermal process to ~6% after, meaning an increase from ~1 to ~15 of the atomic carbon to oxygen ratio (C/O).…”
Section: Resultsmentioning
confidence: 71%